2010
DOI: 10.1186/1475-2875-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of non-artemisinin- and artemisinin-based combination therapies for uncomplicated falciparum malaria in Cameroon

Abstract: BackgroundThe use of drug combinations, including non-artemisinin-based and artemisinin-based combination therapy (ACT), is a novel strategy that enhances therapeutic efficacy and delays the emergence of multidrug-resistant Plasmodium falciparum. Its use is strongly recommended in most sub-Saharan African countries, namely Cameroon, where resistance to chloroquine is widespread and antifolate resistance is emerging.MethodsStudies were conducted in Cameroonian children with acute uncomplicated P. falciparum mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 24 publications
4
41
2
Order By: Relevance
“…The ACPR recorded at day 28 in the AS/SP (83.8%) and AS/AQ (90.2%) groups is in line with a previous study conducted at four different urban centers in Cameroon, where ACPR at day 28 of 88.5% and 88.3% were reported in the AS/SP and AS/AQ groups, respectively [30]. Both combinations demonstrate good activity against the asexual forms of the parasite and, thus, remain effective in the treatment of malaria in Cameroon.…”
Section: Resultssupporting
confidence: 90%
“…The ACPR recorded at day 28 in the AS/SP (83.8%) and AS/AQ (90.2%) groups is in line with a previous study conducted at four different urban centers in Cameroon, where ACPR at day 28 of 88.5% and 88.3% were reported in the AS/SP and AS/AQ groups, respectively [30]. Both combinations demonstrate good activity against the asexual forms of the parasite and, thus, remain effective in the treatment of malaria in Cameroon.…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that adherence to antimalarial agents is inversely proportional to length of therapy and frequency of taking dosages [51]. The complete treatment of uncomplicated malaria requires a patient to take 6 doses of AL as compared to 3 doses for other ACT-based combinations [5]. Despite the increased dosages of AL over AS/AQ, we did not observe a statistically significant difference in adherence to these antimalarial agents.…”
Section: Discussioncontrasting
confidence: 63%
“…Several ACT combinations available include artemether-lumefantrine (AL), artesunate-amodiaquine (AS/AQ), artesunate-mefloquine (AS/MQ), artesunate-chlorproguanil-dapsone (AS/CD), artesunate-sulphadoxine-pyrimethamine (AS/SP), dihydroartemisinin-piperaquine (DA/PQ), artesunate-piperazine (AS/PZ), and artesunate-atovaquone-proguanil (A/AP) [5]. Out of these ACT combinations WHO recommended AL, AS/MQ, AS/AQ, and AS/SP [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently quinine and artemisinin are the two effective drugs obtained from two traditional medicinal plants. Quinine was obtained from the bark of the Cinchona tree [6, 7] and artemisinin from the plant Artemisia annua [8, 9]. However, in the recent years these drugs show some degree of resistance [10, 11].…”
Section: Introductionmentioning
confidence: 99%